USE OF NEURO-LINGUISTICS METHODS IN THE STUDY OF A FOREIGN LANGUAGE («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article examines the application of methods of neurolinguistics in the study of foreign languages. Research in this area helps us better understand how the brain perceives, processes, and absorbs a new language. We will look at key approaches, such as neuroeducation, neuromodulation that help researchers and teachers optimize language learning methods. Understanding the brain mechanisms underlying language learning opens up new opportunities for effective learning and enables personalized learning approaches for the individual student. This article is intended to analyze current trends and prospects for the use of neurolinguistics in the field of language learning.
Keywords: neurolinguistics, method, human brain, practical setting, comprehension, lexical structure.